Ecology, soil and crop management for livelihoods in Ladakh region: An Overview - GUPTA, R. D.; ARORA, SANJAY (Journal of Soil and Water Conservation, 2020)
The Ladakh region is the cold arid region of Jammu and Kashmir state in north India where agriculture is the main occupation. The soils of the region are alkaline, poor in fertility and prone to erosion. The low temperature of the area during most part of the year accompanied with scanty rainfall, low humidity, more evaporation transpiration and soil erosion hazards pose obstacles for agricultural production. The glacial erosion is quite predominant in the cold arid region of Ladakh. Application of organic manures, compost and biofertilizer can improve soil health. Livestock management has great scope for livelihood security. Plantation of agroforestry, medicinal plants, fruits and vegetables can help in management of wastelands and restoration of poor agricultural lands. Soil and water conservation including rainwater harvesting, agronomic measures such as crop rotation, mulching and integrated nutrient management, especially green manuring and mixed use of FYM and fertilizers, are useful in management of soil and water resources for sustaining agricultural production vis-Ã -vis economic upliftment of the farmers in the region.